Vegetation patterns and plant reproductive processes in the succulent Karoo - Esler, Karen Joan (Department of Biological Sciences, 2016)
This thesis focuses on vegetation patterns and plant reproductive processes at the Tierberg Karoo Research Centre (33°1 0'S, 22°17'E) in the semi-arid southern Succulent Karoo, South Africa. It begins with an investigation into the roles of soil properties and competition in explaining variation in species distributions. The aim was to investigate changes in soil properties associated with species turnover (replacement series). Patterns of species abundances have been attributed to cyclic succession driven by disturbance and inter-specific competition. Areas where dominant species replaced each other over apparent edaphic discontinuities were investigated to test the roles of soil properties and competition in explaining variation in species distributions. Only soil pH differed significantly across the gradients studied. However, inter-and intra-specific· competitive interactions were also inferred. It was concluded that species distribution patterns resulted from the combined effects of edaphic factors and competition. The bulk of the thesis focuses on the reproductive biology of key species in the cyclic succession in order to understand the demographic processes underlying these patterns. The vegetation model proposes that heuweltjies (or mima-like mounds) are the source of disturbance which initiates the successional process. A study of reproductive attributes of dominant species occurring on and off heuweltjies indicated that species occurring on heuweltjies had opportunistic life-history traits; seeds did not germinate readily and canopy seed banks were maintained. Species off heuweltjies had higher overall germination and did not maintain seed banks in the plant canopies. The differences in reproductive attributes were related to competition and disturbance.